Kαταλυτική οξείδωση μεθανίου σε χαμηλές θερμοκρασίες σε στηριζόμενους καταλύτες ιριδίου - Ανδρέου, Λουκία (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος,Τεχνολογικό πανεπιστήμιο Κύπρου, 2013)
The present dissertation work concerns the study of the catalytic oxidation of methane over supported Ir and Pt catalysts. This reaction has been studied under relatively low temperature range of 200-450oC, for the decomposition of emitted unburned methane without the simultaneous production of CO. The first chapter is a literature review on the oxidation of methane at low temperatures for metal supported catalysts. Additionally, the theoretical background that concerns the theory over supported catalysts, the activity, the deactivation, the selectivity towards CO2 and the chemical adsorption of CH4 on metals are extensively described in the first chapter. Furthermore, described the wet impregnation method used to prepare the catalysts in the present PD. Also, the methods for the characterization of the supported metal catalysts, such as B.E.T. The second chapter describes the experimental procedure for the synthesis and characterization for both catalytic systems, Ir/Al2O3 and Pt/Al2O3. The activity of the catalysts, the role of the loading of Ir and Pt and the selectivity of the reaction towards carbon dioxide, has been thoroughly studied .Furthermore, describes the flow system used for conducting the catalytic experiments for this P.D. The results and discussion are described in the third chapter. Based on the experimental results of the present work, shows that the 5 w.t.% Ir/Al2O3 catalyst presents the maximum conversion of methane (XCH4=100 %) and highest activity and selectivity (towards CO2 ) at 450oC for the reaction.
Keywords: Methane; Catalysts